Predictors of adherence to influenza vaccination for healthcare workers from a teaching hospital: A study in the prepandemic era - de Souza Cavalcante, Ricardo [UNESP]; Jorge, Aline Maia Zambonatto [UNESP]; Fortaleza, Carlos Magno Castelo Branco [UNESP] (FapUNIFESP (SciELO), 2010)
Introduction: Even before the 2009 pandemics, influenza in healthcare workers (HCW) was a known threat to patient safety, while Influenza vaccine coverage in the same group was generally low. Identification of predictors for HCW adherence to Influenza vaccination has challenged infection control committees. Methods: Our group conducted a cross-sectional survey in December 2007, interviewing 125 HCWs from a teaching hospital to identify adherence predictors for Influenza vaccination. The outcomes of interest were: A - adherence to the 2007 vaccination campaign; B - adherence to at least three yearly campaigns in the past five years. Demographic and professional data were assessed through univariate and multivariate analysis. Results: Of the HCWs interviewed, 43.2% were vaccinated against Influenza in 2007. However, only 34.3% of HCWs working in healthcare for more than five years had adhered to at least three of the last five vaccination campaigns. Multivariate analysis showed that working in a pediatric unit (OR = 7.35, 95%CI = 1.90-28.44, p = 0.004) and number of years in the job (OR = 1.32, 95%CI = 1.00-1.74, p = 0.049) were significant predictors of adherence to the 2007 campaign. Physicians returned the worst outcome performances in A (OR = 0.40, 95%CI = 0.16-0.97, p = 0.04) and B (OR = 0.17, 95%CI = 0.05-0.60, p = 0.006). Conclusions: Strategies to improve adherence to Influenza vaccination should focus on physicians and newly-recruited HCWs. New studies are required to assess the impact of the recent Influenza A pandemics on HCW-directed immunization policies.
Preditores de adesão à vacinação contra influenza em profissionais de um hospital de ensino: Um estudo na era pré-pandêmica
Keywords: Healthcare workers; Influenza; Vaccination